Improving LSB Steganography using Filtering approach along with AES and RSTEG - P I, Sumayya; K, Sheena Kurian (IJRDO -Journal of Computer Science Engineering, 2015)
In steganography, sending a secret message securely through the network is done by hiding the message in acover media. Variant techniques are available for steganography according to the specific needs and the world iscompeting to develop much efficient techniques than the present methods. A new way of securing the data is proposedhere which makes use of the combination of two data securing techniques. The technique improves the security, as themessage is not directly embedded in the cover image, instead a filtering based approach is done. Accordingly a statusis provided in the LSB of the pixel, which helps in retrieving the hidden message. The proposed method uses the MSBbits of pixels for decision making. Multilevel steganography is done by incorporating retransmission steganography.The embedded message is encrypted before embedding which improves the security level. It is effortful for a snooperto retrieve the actual message as it is very different from the common LSB method. It is being found out that theproposed method hides large data in a single image retaining the advantages and discarding the disadvantages of thetraditional LSB method. The Mean Square Error (MSE) and Peak Signal-to-Noise Ratio (PSNR) and the histogramdifferences can be used to measure the image quality and efficiency of the technique.